Adiponectin, Leptin, IGF-1, and Tumor Necrosis Factor Alpha As Potential Serum Biomarkers for Non-Invasive Diagnosis of Colorectal Adenoma in African Americans - Ashktorab, Hassan; Soleimani, Akbar; Nichols, Alexandra; Sodhi, Komal; Laiyemo, Adeyinka O.; Nunlee-Bland, Gail; Nouraie, Seyed Mehdi; Brim, Hassan (Frontiers in Endocrinology, 2018)
The potential role of Adiponectin, Leptin, IGF1, and TNFα as biomarkers in colorectal adenoma is not clear. Therefore, we aimed to investigate the blood serum levels of these biomarkers in colorectal adenoma. The case-control study consisted of serum from 180 African American patients with colon adenoma (cases) and 198 healthy African Americans (controls) at Howard University Hospital. We used ELISA for Adiponectin, Leptin, IGF1 and TNFα detection and quantification. Statistical analysis was performed by t-test and multivariate logistic regression. The respective differences in median Leptin, Adiponectin, IGF1 and TNFα levels between control and case groups (13.9 vs. 16.4), (11.3 vs. 46.0), (4.5 vs. 12.9) and (71.4 vs. 130.8) were statistically significant (p<0.05). In a multivariate model, the odds ratio (ORs) for Adiponectin, TNFα and IGF1 were 2.0 (95% CI=1.6–2.5; P<0.001), 1.5 (95% CI=1.5– 2.0; P 0.004) and 1.6 (95% CI=1.3–2.0; P< 0.001), respectively. There was a positive correlation between serum Adiponectin and IGF1 concentrations with age (r=0.17, P< 0.001 and r=0.13, P=0.009), TNFα, IGF1 and Leptin concentration with Body Mass Index (BMI) (r=0.44, P< 0.001; r=0.11, P=0.03 and r = 0.48, P<0.001), respectively. Also, there was a negative correlation between Adiponectin and Leptin concentrations with BMI (r=-0.40, P<0.001 and), respectively. These data support the hypothesis that Adiponectin, IGF1 and TNFα high levels correlate with higher risk of colon adenoma and can thus be used for colorectal adenomas risk assessment.